2022
DOI: 10.33086/jhs.v15i01.2455
|View full text |Cite
|
Sign up to set email alerts
|

Wet Cupping Therapy to Reduce Total Cholesterol Levels in People with Diabetes

Abstract: Diabetes Mellitus is a condition characterized by an increase in blood glucose levels, accompanied by metabolic abnormalities. Increased blood sugar levels in DM can cause cholesterol levels in the blood to increase, causing atherosclerosis. Management of high cholesterol levels in DM patients is needed to prevent complications. One of non-pharmacological therapy that can be used in DM patients with high cholesterol levels is cupping therapy. The purpose of this study was to determine the effect of cupping the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…total cholesterol levels can decrease 25 . The results of controlled clinical studies also prove that wet cupping can significantly reduce cholesterol, triglyceride, low-density lipoprotein (LDL) and fasting blood glucose levels.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…total cholesterol levels can decrease 25 . The results of controlled clinical studies also prove that wet cupping can significantly reduce cholesterol, triglyceride, low-density lipoprotein (LDL) and fasting blood glucose levels.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…2 In Indonesia, data from Basic Health Research (Riskesdas) reported that there was an increase in the number of hypertension cases from 2013 to 2018. In 2013 the number of hypertension sufferers based on measurements at ages ≥ 18 years was 25.8% and increased in 2018 to 34.1%. The estimated number of hypertension cases in Indonesia is 63,309,620 people with a death rate of 427,218 deaths.…”
Section: Introductionmentioning
confidence: 99%
“…It's usually just known to have hypercholesterolemia when carrying out a health check or because there are other complaints. Hypercholesterolemia must be watched out for because hypercholesterolemia has an impact or other diseases enter the body, such as coronary heart disease, hypertension, impaired liver function, and diabetes (Hapipah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%